Urgensi Revisi Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika Terkait Pemanfaatan Ganja Untuk Kepentingan Medis - Mhd. Badri; Sumaidi Sumaidi; Reza Iswanto (Wajah Hukum, 2026)
Law Number 35 of 2009 concerning Narcotics needs to be revised to legalize the use of medical marijuana as an alternative medical therapy, in order to provide legal certainty for doctors and expand access to treatment for patients based on scientific evidence. This study aims to analyze inconsistencies in the current law and formulate criminal law policies related to the revision of Law Number 35 of 2009 concerning Narcotics. This research method uses a prescriptive approach with a six-month activity plan. The object of the study is the inconsistency between Article 8 of Law Number 35 of 2009 concerning Narcotics and the need for access to medical marijuana treatment. The legal sources used include primary, secondary, and tertiary legal materials. The study was conducted in Indonesia with qualitative analysis. The results of this study are: The inconsistency between Article 8 of Law Number 35 of 2009 concerning Narcotics and the need for access to medical marijuana treatment is a significant issue. This regulation aims to prevent drug abuse, but there is demand from the medical community and patients for research and the use of medical marijuana. Revision of the law is needed so that the use of medical marijuana can be carried out legally, providing legal certainty for health workers and patients.